Study on the Tribological Behaviors of a Wave Glider’s Wing’s Rotating Shaft Using Fractal and Chaotic Analysis - Shihui Lang; Hua Zhu; Xuehai Lian (Lubricants)
This paper conducts wear tests of rotating shafts and bearings, and collects the wear amount, surface morphology, and friction force signals to study its tribological behaviors using the fractal and chaotic analysis. The rotation shaft surface fractal dimension were calculated to characterize the self-similarity and smoothness, the signals’ phase trajectories were constructed, and its correlation dimension and phase-point saturation were calculated to reveal the dynamic evolution of the system. The results show that the surface fractal dimension increases from low to high. The phase trajectory fluctuates and then maintains in a finite space, and the correlation dimension increases and stabilizes near the larger value while the phase-point saturation has the opposite evolution. The changes in surface fractal dimension, phase trajectories, correlation dimension, and phase-point saturation are similar to the wear rate, exhibiting a transition from instability to stability, which is more objective and sensitive than traditional representation methods. According to the fractal and chaotic characterization results of the worn surface and friction force signal, the material of CrNiMoN has better friction and wear properties than GCr15. The results reveal the tribological behaviors and wear mechanisms of the rotating shaft and provide guidance for material selection and designing, along with a basis for characterizing the wear status of the rotating shaft of wave glider wing.